2010
DOI: 10.1007/s12576-010-0114-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of β-adrenergic stimulation and exercise on NR4A3 protein expression in rat skeletal muscle

Abstract: β-Adrenergic stimulation and exercise up-regulate the mRNA expression of nuclear receptor NR4A3, which is involved in the regulation of glucose and fatty acid utilization genes in skeletal muscle. The objective of our study was to examine the effects of β-adrenergic stimulation and exercise on the expression of NR4A3 protein in rat skeletal muscle. A single subcutaneous injection of clenbuterol, which is a β2-adrenergic receptor (β2-AR) agonist, increased NR4A3 mRNA and protein expression in the fast-twitch gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…The most highly induced genes in the exercising leg were all members of the NR4A family, a subgroup of orphan receptors within the nuclear receptor superfamily. NR4A1 and NR4A3 have been reported to be upregulated shortly after acute exercise and during recovery in rat [40], [41], pig [23], and human [24], and this upregulation likely occurs locally by contractile stimuli [40]. This finding was confirmed by our study in which we observed an upregulation of NR4As in the exercising, but not in the non-exercising leg.…”
Section: Discussionsupporting
confidence: 89%
“…The most highly induced genes in the exercising leg were all members of the NR4A family, a subgroup of orphan receptors within the nuclear receptor superfamily. NR4A1 and NR4A3 have been reported to be upregulated shortly after acute exercise and during recovery in rat [40], [41], pig [23], and human [24], and this upregulation likely occurs locally by contractile stimuli [40]. This finding was confirmed by our study in which we observed an upregulation of NR4As in the exercising, but not in the non-exercising leg.…”
Section: Discussionsupporting
confidence: 89%
“…Pearen et al [36, 37] and Kawasaki et al [38] identified that β 2 -AR activation increases the expression of the orphan nuclear receptor, NOR-1 (NR4A3), a negative regulatory factor of myostatin (a member of the transforming growth factor- β superfamily and a potent negative regulator of muscle mass), in fast-twitch muscles without altering that in slow-twitch muscles. Furthermore, Shi et al [32] demonstrate the possibility that β 2 -adrenergic agonist-induced fiber-type-dependent hypertrophy is in part due to the extracellular signal-regulated kinase (ERK)/mitogen activated protein kinase (MAPK) pathway.…”
Section: Pharmacological Stimulation Of β2-armentioning
confidence: 99%
“…Furthermore, many studies have suggested that β2-AR signaling pathways of synthesis and degradation of protein are different between fast and slow muscles, and that this agonist induces hypertrophy in fast muscles rather than in slow muscles [30][31][32][33][34] . These results suggest that the effects of β2-AR stimulation with CLE differed between fast and slow muscles, and that the hypertrophy induced by this agonist occurred more clearly in fast muscles than in slow muscles.…”
Section: Differences In the Effects Of Cle Between Fast And Slow Musclesmentioning
confidence: 99%